PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMK NEGERI 10 KABUPATEN TANGERANG - Wijanarko, Danang; Saleh, Sirajudin; Sufriadi, Sufriadi (Jurnal Riset dan Inovasi Pembelajaran, 2022)
The purpose of this study is to improve the learning outcomes of class X OTKP students at SMK Negeri 10 Tangerang Regency in the Academic Year 2021/2022 in Correspondence subjects with the application of the PBL (Problem Based Learning) learning model. This type of research is Classroom Action Research with descriptive methods, the data analysis technique is quantitative, the average test scores of students' learning outcomes. Data collection techniques for student learning outcomes with learning outcomes tests. This study consisted of 2 cycles consisting of 4 stages. The research subjects were 35 students. The results of this study are the application of the Problem Based Learning learning model can improve student learning outcomes as evidenced by an increase in student learning outcomes in the pre-cycle, increasing in the first cycle and increasing again in the second cycle. All students have completed in learning the material parts of the letter; the forms of letters so that the Problem Based Learning Model is very good to be applied in SMK Negeri 10 Tangerang Regency.